Culturas tradicionais no Ceará: nas dobras de narrativas em contendas sertanejas - Sousa, José Josberto Montenegro (2009)
This work aimed to study traditional cultures of Ceará State, Brazil, with emphasis on the experiences and the way of being and living of poor backwoodsmen population. We agreed to discuss conceptions about the backwoods and backwoodsmen, disseminated by folklorits´ onset, the instance of literacy, of sciences, and public power, that reproduce equivocate apprehension about backwoodsmen s culture which its origin forwards significantly to indigenous and African cultural heritage. These affirmations are marked by persistent strategies kept as expressions of popular culture. We analyzed the dimension of their argument and point of views, giving privilege to the narratives produced about and by backwoodsmen, with the objective to evidence distinct perspectives of its statement s content